2008
DOI: 10.1111/j.1360-0443.2008.02292.x
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana withdrawal and craving: influence of the cannabinoid receptor 1 (CNR1) and fatty acid amide hydrolase (FAAH) genes

Abstract: Aim To examine whether withdrawal after abstinence and cue-elicited craving were associated with polymorphisms within two genes involved in regulating the endocannabinoid system, cannabinoid receptor 1 (CNR1) and fatty acid amide hydrolase (FAAH). Two single nucleotide polymorphisms (SNPs) in the CNR1 (rs2023239) and FAAH (rs324420) genes, associated previously with substance abuse and functional changes in cannabinoid regulation, were examined in a sample of daily marijuana smokers. Participants Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(155 citation statements)
references
References 50 publications
9
141
3
2
Order By: Relevance
“…In addition to our previous findings of association between rs202329 variance and cannabis withdrawal, craving, and cue-elicited brain activation (Filbey et al, 2010;Haughey et al, 2008), this SNP has been associated with other SUD intermediate phenotypes, including greater alcohol cue-elicited brain activation and greater subjective reward after consuming alcohol , greater alcohol craving at higher levels of alcohol consumption (van den Wildenberg et al, 2007), greater trait impulsivity (Ehlers et al, 2007), and, as part of a haplotype block with other CNR1 SNPs, greater severity of nicotine dependence (Chen et al, 2008). Although these other studies did not report participants' cannabis use, it is highly comorbid with alcohol and nicotine use.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to our previous findings of association between rs202329 variance and cannabis withdrawal, craving, and cue-elicited brain activation (Filbey et al, 2010;Haughey et al, 2008), this SNP has been associated with other SUD intermediate phenotypes, including greater alcohol cue-elicited brain activation and greater subjective reward after consuming alcohol , greater alcohol craving at higher levels of alcohol consumption (van den Wildenberg et al, 2007), greater trait impulsivity (Ehlers et al, 2007), and, as part of a haplotype block with other CNR1 SNPs, greater severity of nicotine dependence (Chen et al, 2008). Although these other studies did not report participants' cannabis use, it is highly comorbid with alcohol and nicotine use.…”
Section: Discussionmentioning
confidence: 85%
“…For example, auditory-presented imagery scripts induce craving in marijuana smokers, and the magnitude of this craving varies as a function of the amount of marijuana-related content presented in the script (43). Craving also increases when abstinent frequent marijuana users are exposed to an auditory script that is paired with a tactile cue, such as a used marijuana pipe or bong (41,42). Importantly, in this paradigm, cue presentation increases craving beyond the effects induced by abstinence.…”
mentioning
confidence: 98%
“…Nevertheless, other studies have shown that CNR1 variants are associated with depression remission after only 12 weeks (Mitjans et al, 2013). Previous association studies which have investigated CNR1 rs2023239 polymorphisms have tested the relationship of these variants to cannabis withdrawal (Haughey et al, 2008), impulsivity (Ehlers et al, 2007) and metabolic syndrome in patients with schizophrenia (Yu et al, 2013) as well as in the general population (Milewicz et al, 2011;Lenarcik-Kabza et al, 2014). On the other hand, the significant interaction in patients homozygous for the G allele in rs1049353, the at-risk allele T for rs1535255 and the T/C for rs20233239 polymorphism yielded significantly higher SAPS scores after 3 years compared with SAPS scores in the other patients.…”
Section: Cnr1mentioning
confidence: 95%